Closed loop speed control of induction generator with scalar-control inverters - Upasan,A. (Elsevier BV, 2015)
A closed loop speed control for an induction generator is presented. The system was developed for a space vector modulation-voltage source inverter and the three-phase squirrel-cage induction generator to regulate speed and generator voltages with scalar control technique. The aim of this research was to a generated voltage with a constant speed at variable mechanical torque of prime mover. The simulation results show a good performance of the system can be achieved by the proposed speed controller. © 2013 The Authors. Published by Elsevier B.V.